Perancangan Sistem Informasi Pada UMKM Ikan Hias Nusatic - Muhammad Hilmy Adhiansyah; Sukanta, Sukanta (Universitas Nusantara PGRI Kediri, 2023)
In the trading business world, namely the business of selling a product, many obstacles are found in processing data such as incoming and outgoing goods, because there are still companies that use manual systems that have not been computerized, the data processing system in the business world today is one of the most dominant problems in the business sector engaged in community services. This research aims to simplify the decision-making process so that it can utilize more effective and efficient cost, effort, and time in Nusatic UMKM. By using the prototype method to realize the desired software model, this application can simplify administrative activities which include sales data, purchasing data, and delivery in stages starting from the registration process to payment transactions.